Dermatoglyphics - A predictor of disease - Tewari, Jay; Tewari, Vineeta; Munsif, Tahsin; Kapoor, Prince; Tewari, Ajoy (Asian Journal of Medical Sciences, 2022)
Dermatoglyphics is the scientific study of the pattern of dermal ridges on the palmar surface of digits, palm and sole. Characteristically, hair does not grow in this area. These ridges serve well to enhance contact. The development of these ridges and the development of the nervous system occur simultaneously in the intrauterine period. The pattern of dermal ridges begins to develop around the 13th week and is completed by the 19th week of intrauterine life. Once the fingerprint pattern develops, it does not change and persists throughout life. Unusual dermatoglyphic patterns often relate to genetic disorders. Dermatoglyphics may be used as an additional screening tool to identify early risk factors that may help prevent additional complications of various diseases. In this review, we will be discussing dermatoglyphics and its important role in the diagnosis of diseases which have some genetic basis.